Citizen engagement with open government data: Lessons learned from Indonesia's presidential election. Issue 1 (31st January 2020) - Purwanto, Arie; Zuiderwijk, Anneke; Janssen, Marijn
Abstract : Purpose: Citizen engagement is key to the success of many Open Government Data (OGD) initiatives. However, not much is known regarding how this type of engagement emerges. This study aims to investigate the necessary conditions for the emergence of citizen-led engagement with OGD and to identify which factors stimulate this type of engagement. Design/methodology/approach: First, the authors created a systematic overview of the literature to develop a conceptual model of conditions and factors of OGD citizen engagement at the societal, organizational and individual level. Second, the authors used the conceptual model to systematically study citizens' engagement in the case of a particular OGD initiative, namely, the digitization of presidential election results data in Indonesia in 2014. The authors used multiple information sources, including interviews and documents, to explore the conditions and factors of OGD citizen-led engagement in this case. Findings: From the literature the authors identified five conditions for the emergence of OGD citizen-led engagement as follows: the availability of a legal and political framework that grants a mandate to open up government data, sufficient budgetary resources allocated for OGD provision, the availability of OGD feedback mechanisms, citizens' perceived ease of engagement and motivated citizens. In the literature, the authors found six factors contributing to OGD engagement as follows: democratic culture, the availability of supporting institutional arrangements, the technical factors of OGD provision, the availability of citizens' resources, the influence of social relationships and citizens' perceived data quality. Some of these conditions and factors were found to be less important in the studied case, namely, citizens' perceived ease of engagement and citizens' perceived data quality. Moreover, the authors found several new conditions that were not mentioned in the studied literature, namely, citizens' sense of urgency, competition among citizen-led OGD engagement initiatives, the diversity of citizens' skills and capabilities and the intensive use of social media. The difference between the conditions and factors that played an important role in the case and those derived from the literature review might be because of the type of OGD engagement that the authors studied, namely, citizen-led engagement, without any government involvement. Research limitations/implications: The findings are derived using a single case study approach. Future research can investigate multiple cases and compare the conditions and factors for citizen-led engagement with OGD in different contexts. Practical implications: The conditions and factors for citizen-led engagement with OGD have been evaluated in practice and discussed with public managers and practitioners through interviews. Governmental organizations should prioritize and stimulate those conditions and factors that enhance OGD citizen engagement to create more value with OGD. Originality/value: While some research on government-led engagement with OGD exists, there is hardly any research on citizen-led engagement with OGD. This study is the first to develop a conceptual model of necessary conditions and factors for citizen engagement with OGD. Furthermore, the authors applied the developed multilevel conceptual model to a case study and gathered empirical evidence of OGD engagement and its contributions to solving societal problems, rather than staying at the conceptual level. This research can be used to investigate citizen engagement with OGD in other cases and offers possibilities for systematic cross-case lesson-drawing.